Enhancing problem-solving skills and creative thinking abilities in U-13 soccer players: the impact of rondo possession games’ training - Bouzouraa, Mohamed Mansour; Dhahbi, Wissem; Ghouili, Hatem; Hamaidi, Jaouher; Ben Aissa, Mohamed; Dergaa, Ismail; Guelmami, Noomen; Souissi, Nizar; Weiss, Katja; Rosemann, Thomas; Zghibi, Makrem; Chamari, Karim; et al. (Biology of Sport, 2025)
To investigate the impact of Rondo possession games, played in different field geometries with complex rules, on the development of problem-solving skills and creative thinking abilities in U-13 youth soccer players. In a repeated-measures and a randomized controlled trial study design, twenty-four competitive young male U-13 soccer players were split into: the training (TG, n = 12) and control (CG, n = 12) groups (matched for age, body height body mass index; and training experience; with weekly training of ~5.5 hours/week for both groups). TG performed a training programme once a week for 8 weeks integrating Rondo possession games with periodized variations, such as player formats, field shapes, duration, pitch sizes, and rest times. Torrance Tests of Creative Thinking (TTCT) – Graphic-Figural-Creativity (abstractness-title, resistance-closure, originality, elaboration, and fluency – GFC), Problem Solving-Inventory (problem-solving-confidence, approachavoidance-style and personal-control – PSI) and Verbal-Creativity (flexibility, originality, fluency – VC) – were performed over time and between groups. We observed significant main effects of time ( p < 0.001–0.005, ƞ 2 p: 0.30–0.76 [ large ]) and group ( p < 0.001–0.002, ƞ 2 p: 0.36–0.60 [ large ]), as well as a significant interaction effect of time×group ( p : < 0.001–0.013, ƞ 2 p: 0.24–0.48 [ large ]) of all GFC, PSI and VC test indices. In the TG group, all TTCT indices showed significant improvement in all indices at the post-test compared to pre-test (-29.90%-227.27%, d: 1.03–4.66 [ large ]). This study showed that 8 weeks of integrated Rondo possession games with structured geometric variations and rule complexity significantly boosted problem-solving skills and creative thinking in U-13 soccer players. These findings suggest a promising direction for youth soccer training, focusing on developing well-rounded players capable of intelligent and flexible gameplay in diverse scenarios.